KESADARAN KONSUMEN TERHADAP PRODUK MAKANAN SNACK UMKM BERSERTIFIKASI HALAL DI KOTA BANDUNG - Cucu Winesi, - (2019)
This study is motivated by the majority of Muslim consumers in Bandung. This influences the supply and the demand of the halal-certified food products. This is in line with the rapid development of the SMEs snacks. This study aims to find out the relation of the consumer awareness factors of the halal-certified food towards the halal-certified SMEs snacks products in Bandung. Five factors that have been tested are religious beliefs, the role of the halal certification, information, health, and self-identity. The method used in this study is quantitative. This study is a survey study which uses questionnaire as the instrument with 100 respondents. The targeted populations are consumers who have consumed the halal-certified SMEs snacks products in Bandung. The sampling technique used in this study is the purposive sampling method. This study found that, partially, there are five factors which influence the consumer awareness of the halal-certified SMEs snacks products in Bandung namely the religious beliefs, the role of the halal certification, information, health, and self-identity. Moreover, simultaneously, those five factors influence the consumer awareness of the halal-certified SMEs snacks products in Bandung significantly. The continuum line of the consumer awareness of halal food is very high. It is expected for the future study to analyze other factors that have not been examined in this study since the influence of the variables studied is 58.7% while the remaining 41.3% are other variables which are not examined in this study.